Exploring the connection between attitudes towards new chinglish and social media among Chinese college students - Liu Xiaoman; Esther Jawing; Zhao Xiaofang (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2024)
New Chinglish has emerged as an undeniable and popular trend on Chinese social media platforms, particularly among Chinese college students. These college students are not only the main force of English users and learners in China but also the major netizens on Chinese social media platforms. However, within a cultural context where ‘standards and adherence to norms have traditionally been of paramount importance to the Chinese’ (Kirkpatrick, 2017: 278), the conflicting attitudes and use towards either upholding traditional viewpoints or adopting opposing stances regarding the New Chinglish warrant intriguing and meaningful exploration. Thus, this study aims to explore the connection between their attitudes towards New Chinglish and its usage behaviors on social media among Chinese college students. It seeks to unveil the reasons underlying their attitudes towards the use of New Chinglish. The indepth exploration reveals a contradictory and uncertain evaluation of their usage of New Chinglish on social media, despite its high level of understandability and acceptability among them. Personal acceptability and preference do not solely determine their attitudes towards their use of New Chinglish on social media; instead, various social factors, such as language inequality, influence their language use behavior and attitudes, leading to a compromise between individual preferences and social influences. Specifically, this study offers insight into the genuine reactions and usage tendencies of English in real-life situations, indicating the future trends in English language development in China.